Mademoiselle Louise; life of Louise de Marillac. - Dollen, Charles ([Boston] St. Paul Editions, 1967)
A biography of a prominent French woman of the seventeenth century who, under the guidance of St. Vincent de Paul, trained the first Sisters of Charity to care for the poor and sick.
Keywords: Louise de Marillac, -- Saint, -- 1591-1660 -- Juvenile literature; Louise de Marillac, -- Saint, -- 1591-1660.